Geological Structures Appearances and Its Relation to Mechanism of Arc-Continent Collision Northen Alor-Wetar Islands - Subarsyah Subarsyah; Riza Rahardiawan (BULLETIN OF THE MARINE GEOLOGY, 2016)
Study area is located in South Banda Basin near the triple junction between Eurasian, Pacific and Indo-Australian Plates. This area is part of back-arc thrusting zone that evolved to compensate convergence between Australia Continent and Banda Arc. Based on seismic section in this area, geological structure analysis is characterized into three distinctive zones. There are Thrust Zone (TZ), Proto Thrust Zone (PTZ) and Normal Fault Zone (NFZ). TZ is defined by distribution of numerous of thrust fault, PTZ contains a blind zone or folds instead of thrust fault, and NFZ defined by distribution of numerous normal fault in the upper portion of seismic section. PTZ identified at several seismic section along the bending zone of oceanic crust. The appearances of bending zone will be easily understood by comprehend the driving mechanism of Australia Continent to the Northeast. The bending zone also related to geometry and tectonic stress of collision. Based on this mechanism it was clearly understood why the western end of study area was not identified the bending zone but it probably the initial process of bending. Contradictive to the western end, the eastern part was clearly shown the bending zone that assumed to have the biggest tectonic stress at this moment. Map of structural analysis also explain that PTZ getting narrow towards the west as the indicator of less of tectonic stress.Keywords: Arc-Continent Collision, Proto Thrust Zone, Wetar, Back arc Thrusting, Banda Sea. Lokasi penelitian berada pada Cekungan Banda Selatan sekitar area triple junction antara Lempeng Eurasia, Pasifik dan Indo-Australia.Daerah ini merupakan bagian dari zona back-arc thrusting yang berkembang sebagai kompensasi dari konvergensi antara kontinen Austalia dan Busur Banda.Berdasarkan penampang seismik di daerah ini analisis struktur geologi dikelompokan kedalam tiga zona. Tiga zona tersebut meliputi Thrust Zone (TZ), Proto Thrust Zone (PTZ) and Normal Fault Zone (NFZ). TZ didefinisikan oleh distribusi dari sejumlah sesar naik, PTZ mengandung sejumlah blind thrust atau lipatan pengganti sesar naik dan NFZ didefinisikan oleh distribusi dari sejumlah sesar normal pada bagian atas dari penampang seismik. PTZ teridentifikasi pada beberapa penampang seismic sepanjang zona bending dari lempeng oseanik. Kenampakan dari zona bending akan mudah dipahami dengan mengetahui mekanisme pergerakan dari kontinen Australia ke arah timurlaut. Zona ini umumnya berhubungan dengan bentuk geometri dan besaran dari tectonic stress dari tumbukan. Berdasarkan mekanisme ini dapat dipahami dengan jelas mengapa bagian ujung barat dari daerah penelitian tidak teridentifikasi zona bending. Kontradiktif terhadap ujung barat, ujung timur memperlihatkan zona bending yang sangat jelas yang diperkirakan mempunyai tectonic stress yang paling besar pada saat ini. Peta dari analisis struktur juga menjelaskan bahwa zona PTZ semakin ke arah barat semakin menyempit sebagai indicator dari berkurangnya tectonic stress.Kata Kunci: Tumbukan Busur-Kontinen, Proto Thrust Zone, Wetar, Back arc Thrusting, Banda Sea.